ChemInform Abstract: Microwave Assisted Synthesis of Dihydrobenzo[4, 5]imidazo[1, 2‐a]pyrimidin‐4‐ones; Synthesis, in vitro Antimicrobial and Anticancer Activities of Novel Coumarin Substituted Dihydrobenzo[4, 5]imidazo[1, 2‐a]pyrimidin‐4‐ones. Issue 15 (15th April 2014) - Puttaraju, Kallimeledoddi B.; Shivashankar, Kalegowda; Chandra, Chandra; Mahendra, M.; Rasal, Vijaykumar P.; Vivek, Ponnuru N. Venkata; Rai, Khushboo; Chanu, Maibam Beebina
Abstract Most of the synthesized title compounds (V) (8 examples) exhibit good antibacterial, antifungal, and cytotoxic activities.